Cutting Edge: Circulating Plasmablasts Induce the Differentiation of Human T Follicular Helper Cells via IL-6 Production - Chavele, Konstantia-Maria; Merry, Eve; Ehrenstein, Michael R (The Journal of immunology (1950), 2015)
B cells require CD4+ T follicular helper (Tfh) cells to progress through the germinal center and provide protective Ab responses. In this article, we reveal a reciprocal interaction whereby circulating human plasmablasts are potent inducers of the Tfh cell–differentiation program, including the expression of their key transcription factor Bcl-6. The markedly increased propensity of plasmablasts, compared with naive B cells, to induce Tfh cell differentiation was due to their increased production of IL-6. Specific targeting of IL-6 using tocilizumab therapy in patients with rheumatoid arthritis led to a significant reduction in circulating Tfh cell numbers and IL-21 production, which was correlated with reduced plasmablast formation. Our data uncover a positive-feedback loop between circulating plasmablasts and Tfh cells that could sustain autoimmunity and spread Ab-driven inflammation to unaffected sites; this represents an important therapeutic target, as well as reveals a novel mechanism of action for tocilizumab.